Ceausescu's population policy: a moral or an economic choice between compulsory and voluntary incentivised motherhood? - Florin Stanica Soare (European Journal of Government and Economics (EJGE), 2013)
The purpose of this paper is to explain why, in 1966, the Romanian leadership adopted a wholly restrictive pronatalist policy, based on the strict limitation of abortion, instead of one based on socioeconomic incentives to families, as suggested by technocrats. Previous literature shows disagreement on whether the choice was motivated by moralistic or economic considerations. In order to find an answer to this question, hundreds of pages of archival material unpublished so far have been analysed, including the minutes of the Central Committee of the Communist Party, statistics, documents identified in the Ministry of Health Archive, and the technical reports that were on the table at the time of the decision. The conclusion of this study, drawn on the basis of these documents, indicates that at the time of 1966, regardless of the suggestions of the technocrats, a decision had already been taken by Ceausescu himself. This decision was influenced directly by economic considerations, namely the wish to obtain the maximum pronatalist effect at a minimum budgetary cost.
Keywords: 330; pronatalist policy; abortion; Romanian Communist Party; birth rate